1996
DOI: 10.1159/000099816
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation Effects on the Metabolism of Metastatic Brain Tumors: Analysis by Positron Emission Tomography and <sup>1</sup>H-Magnetic Resonance Spectroscopy

Abstract: To evaluate irradiation effects on the metabolism of metastatic brain tumors treated by Gamma Knife radiosurgery, positron emission tomography (PET) and 1H-magnetic resonance spectroscopy (MRS) studies were performed on five patients. The tumor origins were lung cancer in three patients and breast cancer in two. Treatment volume was 0.4–10.1 cm3 (mean: 5.5 cm3). The marginal dose to the tumor was 24–30 Gy (mean: 26.2 Gy). The follow-up period was 5–19 months (mean: 13.4 months)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…By contrast, tumor progression was associated with prominent metabolic alterations, such as decrease of NAA content, NAA/Cho ratio and Cr content, and increase of Lip/nCr ratio and Cho content. This confirms the appropriateness of 1 H-MRS for diagnosis of local recurrence of intracranial metastases after SRS 9,10,27,29,32 . Moreover, analysis of the serial metabolic data in progressing lesions revealed several subtle neurochemical alterations before volumetric changes in the neoplasm.…”
Section: Metabolic Changes In Progressing Lesionssupporting
confidence: 70%
See 2 more Smart Citations
“…By contrast, tumor progression was associated with prominent metabolic alterations, such as decrease of NAA content, NAA/Cho ratio and Cr content, and increase of Lip/nCr ratio and Cho content. This confirms the appropriateness of 1 H-MRS for diagnosis of local recurrence of intracranial metastases after SRS 9,10,27,29,32 . Moreover, analysis of the serial metabolic data in progressing lesions revealed several subtle neurochemical alterations before volumetric changes in the neoplasm.…”
Section: Metabolic Changes In Progressing Lesionssupporting
confidence: 70%
“…Previously we found that initial decreases of Cho and NAA can be identified as early as 16-18 hours after treatment 7 . Others observed decreases of Cho, Lac or Lip and increases in NAA on MR spectra of metastatic adenocarcinoma within the first week after SRS 29,30 . In the series of Kimura et al 31 the effects of irradiation were marked on 1 H-MRS of brain metastases on average 2.8±1.6 weeks after radiosurgery and were observed earlier than changes in 201 TlCl single photon emission computed tomography and gadoliniumcurrent gliomas 23,24 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Studies that compare techniques, however, are few and have conflicting results. Some authors suggested that using PET and MRS in conjunction may help distinguish tumor recurrence from necrosis (39). Others have not found significant advantages in using PET versus thallium-201 SPECT (40).…”
Section: Figurementioning
confidence: 99%
“…Coupled with magnetic resonance imaging techniques, it allows for the corre-lation of anatomical and physiological changes in the metabolic and biochemical processes occurring within previously-determined volumes in the brain. 13 Proton magnetic resonance spectroscopy of the brain is useful whenever biochemical or metabolic assessment may be necessary, such as in differential diagnosis of focal brain lesions (neoplastic and non-neoplastic diseases); [14][15][16][17][18][19][20] brain lesions in patients with acquired immunodeficiency syndrome; [21][22][23] diagnosis of dementia [24][25][26] and other degenerative diseases; 27 follow-up radiation therapy for patients with brain neoplasms; [28][29][30] demyelinating diseases such as multiple sclerosis [31][32][33] and leukodystrophy; 6,34 diagnosis and prognosis of brain ischemic 35,36 and traumatic lesions; [37][38][39][40][41][42] assessment of epilepsy; [43][44][45] biochemical alterations in hepatic encephalopathies; 46,47 and neuropediatric affections such as brain tumors, inborn errors of metabolism and hypoxic encephalopathy. [48][49][50] Magnetic resonance examinations, including spectroscopy, are absolutely contraindicated in patients with heart pacemakers or other electronic appliances implanted in the body, and thos...…”
Section: In Vivo Proton Magnetic Resonance Spectroscopymentioning
confidence: 99%